A hybrid weakly nonconforming discretization for linear elasticity. Issue 1 (25th October 2016) - Krämer, Julian; Wieners, Christian; Wohlmuth, Barbara; Wunderlich, Linus
Abstract: We introduce a hybridizable discretization for problems of linear elasticity, based on a flexible weak coupling of the displacement and the normal stress across the inner element boundaries. The dual variables of the Lagrange multiplier are introduced as hybrid trace variables. A reduction of the equation system to these variables allows for an efficient parallel implementation. The performance of an adaptive choice of the hybrid degrees of freedom is demonstrated by a numerical example with a corner singularity. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)